Bedaquiline for the treatment of drug-resistant tuberculosis. Issue 5 (May 2015) - Bélard, Sabine; Heuvelings, Charlotte C; Janssen, Saskia; Grobusch, Martin P
<x xml:space="preserve">Abstract</x> Bedaquiline is a much-needed novel drug which is highly effective against drug-resistant tuberculosis. While its clinical development has been laudably fast-tracked and the drug is now available for inclusion into treatment regimens when no suitable alternatives exist, clinical experience with bedaquiline is still limited. Phase III trial data and Phase IV studies are needed particularly to study different patient populations and to optimize treatment regimens. Drug resistance to bedaquiline needs to be monitored carefully, and full access to bedaquiline treatment where it is appropriate and needed must be promoted.